Conceptualizing Green Human Resource Management in Predicting Employees' Green Intention and Behaviour : A Conceptual Framework - Mukherjee, Bidhan; Chandra, Bibhas (Prabandhan: Indian Journal of Management, 2018)
In the era of globalization, environmental concerns have become a great threat to the earth and its mankind. Within this realm, the need to integrate environmental management into HRM termed as green HRM has gained augmented attention. Green HRM (abbreviated as GHRM) is a pronunciamento which assists in creating green employees who can recognize and acknowledge green ethos in any organizational setup. However, employees' behaviour is a significant facet that can enhance organizational productivity and performance, and GHRM has been conceptualized to influence employees' green behaviour. But how that behaviour is predicted or influenced through GHRM is not explored fully, and due to a dearth of a dominant model in understanding and predicting employees' behaviour in an organization, there are calls for further research to strengthen the existing knowledge. Literature has substantiated the importance of adopting GHRM practices and policies, but scholars have validated that the volume of scholarly work focusing on green HRM remains very small and needs further research to strengthen the field theoretically and empirically. Against this backdrop, a conceptualized framework was proposed in this study based on extant literature review to understand and predict employee behaviour in an organization as a whole or explicitly in a workplace.